The foundational influence of early spiritual experiences on adulthood - M. O'Sullivan (Acta Theologica)
This article presents research on spiritual experience in childhood and aims to illustrate the foundational effects of such experience on adult lives, using the qualitative data of several testimonies. The latter highlight that researchers in spirituality need to pay more attention to what is happening at a spiritual level in childhood and to the hermeneutical lens it provides for interpreting the lives of adults, including themselves, who once were children. They will also illustrate the role religious socialisation plays in spiritual experiences in childhood. The stories are explained in terms of the spirituality framework of the foundational desire for authenticity in the subjectivity of the child interacting with the child’s lived historical situation and how this interaction continues to play out in the life of the adult. They are evidence of the self-implicating character of research in spirituality as the researcher was also once This article presents research on spiritual experience in childhood and aims to illustrate the foundational effects of such experience on adult lives, using the qualitative data of several testimonies. The latter highlight that researchers in spirituality need to pay more attention to what is happening at a spiritual level in childhood and to the hermeneutical lens it provides for interpreting the livesof adults, including themselves, who once were children. They will also illustrate the role religious socialisation plays in spiritual experiences in childhood. The stories are explained in terms of the spirituality framework of the foundational desire for authenticity in the subjectivity of the child interacting with the child’s lived historical situation and how this interaction continues to play out in the life of the adult. They are evidence of the self-implicating character of research in spirituality as the researcher was also once a child. The researcher regards authentic subjectivity as a form of mystagogical method, a method about which Kees Waaijman has written eloquently.